Мир Книги джунглей: научное издание: пер. со швед. / Я. Линдблад ; пер. со швед. Л. Л. Жданова - Линдблад Ян (Мир, 1983)
Экземпляры: (20190813) / Инвентарный номер: 8304z2 / Цена: 5.00 / Сис.шифр: 28.6 / Авт.знак: Л 59 / ББК: 28.693.36(5Инд)